Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Komitmen Organisasi dan Kinerja Pegawai Universtas Nahdlatul Ulama Surakarta - Kristiani, Endah (STIE Surakarta, 2015)
This study aims are to determine the effect of leadership, organizational culture on theÂ performanceÂ ofÂ employeesÂ inÂ theÂ UnivercityÂ ofÂ NahdlatulÂ UlamaÂ SurakartaÂ with commitment as an intervening variable. Â Data analysis techniques used path analysisÂ (path analysis ),Â whichÂ will be tested with theÂ t test, F test and test R2 Â , Correlations, direct effect and indirect effect and total effect. TheÂ techniqueÂ ofÂ collectingÂ dataÂ usingÂ questionnaires,Â theÂ sampleÂ areÂ employes at the Univercity of Nahdlatul Ulama Surakarta as many as 30 respondents. T- testÂ resultÂ showedÂ leadershipÂ hasÂ positiveÂ andÂ significantÂ impactÂ onÂ employee commitment,Â organizationalÂ cultureÂ hasÂ positiveÂ Â andÂ insignificantÂ Â Â effectÂ onÂ employee commitment.Â AsÂ forÂ variableÂ leadershipÂ Â Â andÂ commitmentÂ haveÂ aÂ positiveÂ and significantÂ effectÂ onÂ theÂ performance,Â organizationalÂ cultureÂ hasÂ positiveÂ and insignificantÂ effectÂ onÂ theÂ performanceÂ ofÂ employeesÂ inÂ theÂ UnivercityÂ ofÂ Nahdlatul Ulama Surakarta. F test showed simultaneously leadership, organizational culture and commitmentâsÂ organizationsÂ hasÂ significantÂ positiveÂ effectÂ onÂ theÂ performanceÂ of employees in the Univercity of Nahdlatul Ulama Surakarta. The value of the coefficient ofÂ determinasiÂ RÂ squareÂ ofÂ 0,9413orÂ 94,13%.Â ThisÂ meansÂ thatÂ theÂ employeeâs performanceÂ isÂ explainedÂ byÂ theÂ variableÂ leadership,Â organizationalÂ cultureÂ and commitmentÂ asÂ anÂ interveningÂ variableÂ ofÂ 94,13Â %Â andÂ theÂ remainingÂ 5,87Â %Â is explained by other variables outside our model, such as work environment, competence and others.